2021
DOI: 10.1093/ofid/ofab096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2 Lateral Flow Rapid Tests in the Diagnosis of Chagas Disease in the Washington Metropolitan Area

Abstract: We compared the accuracy of the Stat-Pak and Chagas Detect Plus to a Latent Class Analysis. A sensitivity of 89.7% and 91.9% and specificity of 97.1% and 80.3%, respectively was seen in the serodiagnosis of Chagas disease in Hispanic immigrants, revealing the limitations of these tests in diverse populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Most of these works used whole blood for the CSP testing and either serum or plasma for conventional serological assays taken as reference. As previously mentioned, detection performance varied among municipalities, with sensibility and specificity ranging from 93.4 to 100.0% and from 97.3 to 99.3%, respectively [28,[31][32][33]. Noteworthily, lower sensitivities were obtained by Roddy et al and Chippaux et al when working with age groups ranging from 9 months to 17.9 years old (93.4%) and from 11 to 20 years old (89.2%), respectively [32,33].…”
Section: Performance Of Immunochromatographic Rapid Tests Commerciall...mentioning
confidence: 87%
See 1 more Smart Citation
“…Most of these works used whole blood for the CSP testing and either serum or plasma for conventional serological assays taken as reference. As previously mentioned, detection performance varied among municipalities, with sensibility and specificity ranging from 93.4 to 100.0% and from 97.3 to 99.3%, respectively [28,[31][32][33]. Noteworthily, lower sensitivities were obtained by Roddy et al and Chippaux et al when working with age groups ranging from 9 months to 17.9 years old (93.4%) and from 11 to 20 years old (89.2%), respectively [32,33].…”
Section: Performance Of Immunochromatographic Rapid Tests Commerciall...mentioning
confidence: 87%
“…Nonetheless, in 2005, the Chagas National Program of Bolivia incorporated the use of a specific rapid test (Chagas Stat-Pak, Chembio Inc.) as the frontline method in both clinical practice and seroepidemiological surveys [31]. Notably, Chagas Stat-Pak (CSP) has shown sensitivity and specificity ranging from 93.4 to 100.0% and from 97.3 to 99.3%, respectively, among Bolivian municipalities [28,[31][32][33]. However, to follow the recommended diagnosis algorithm, positive cases still must be confirmed by a conventional immunoassay [31].…”
Section: Applicability Of Rapids Tests and Its Perspectives In CD Con...mentioning
confidence: 99%
“…This study was performed under the ethics committee of the Johns Hopkins School of Public Health (protocol IRB 6713) and all patients provided written informed consent. From February 2016 to April 2018, patients originally from Chagas-endemic countries were recruited from health fairs and recruitment events held at various churches, community centers, and consulates, in Virginia, Maryland and Washington D.C[32, 33]. Patients provided a blood sample and underwent a cardiovascular evaluation consisting of a clinical examination, electrocardiogram (EKG) and echocardiogram.…”
Section: Methodsmentioning
confidence: 99%
“…The IgG-TESA-blot was developed and performed using the trypomastigote excreted-secreted antigen from the T. cruzi Y strain [36, 37]. Individuals with positive results on two or more tests were considered seropositive for Chagas disease[32, 33]. 10 Chagas-positive patients were randomly selected, and 23 Chagas-negative patients were matched by age, sex, region of origin, and cardiac disease stage.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a sensitivity of 30% has been reported for Chagas Stat Pak in samples from Peru [ 13 ]; but an overall sensitivity of 87% was found in Bolivian samples [ 13 , 14 ]. Chagas Detect Plus, the only rapid test currently approved by the FDA, was shown to have variable performance according to geographic region [ 15 , 16 ]. In a study performed on US blood donors, this rapid test showed the highest sensitivities for those donors born in South America, the lowest sensitivities for those born in Mexico, and intermediate sensitivities for those born in Central America [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%